Hedonic Value in Customer Satisfaction: A Bibliometric Analysis - Radina Noorsahadita; Lissa Rosdiana Noer (Dinasti International Journal of Education Management And Social Science, 2025)
This study systematically maps research on hedonic value and customer satisfaction using a bibliometric approach, in order to identify dominant themes, research gaps, and key contributions in the field. Bibliometric analysis was conducted using the Scopus database, focusing on articles discussing "hedonic value" and "customer satisfaction" between 2002 and 2025. The PRISMA protocol was applied in the screening and selection process, resulting in 55 relevant articles. The analysis shows an increase in research interest since 2018, with keywords such as "customer satisfaction," "perceived enjoyment," and "emotional value" as the focus. Two main clusters identified include a focus on sales and consumer behavior. These findings also reflect the high level of international collaboration and the dominance of recent literature, confirming the topic's relevance in current academic discourse. This study contributes to the consumer behavior literature by providing a structured overview of the relationship between hedonic value and customer satisfaction, as well as identifying directions and opportunities for further research in marketing and consumer psychology.